Sulforaphane attenuates aldose reductase-mediated platelet dysfunction in high glucose-stimulated human platelets via downregulation of the Src/ROS/p53 signaling pathway - Bi, Xiaoyan; Huang, Xinhui; Zhang, Chunmei; Zhao, Xin; Ma, Junyu; Li, Mengyao; Li, Xuexun; Zeng, Bangzhao; Li, Rong; Zhang, Xian; Ya, Fuli (Frontiers in Nutrition, 2025)
BackgroundPlatelet abnormalities are well-recognized complications of type 2 diabetes mellitus (T2DM). High glucose (HG) increases platelet mitochondrial dysfunction, apoptosis and hyperreactivity in T2DM, which underlie the occurrence of thrombotic events. Sulforaphane (SFN) is a dietary isothiocyanate enriched in cruciferous vegetables and possesses multiple biological activities. This study aimed to explore the efficacy of SFN on platelet dysfunction in HG-stimulated human platelets in vitro.MethodsWashed human platelets from healthy donors were pre-incubated with SFN (5, 10, or 20 μM) or vehicle control (0.05% DMSO) for 40 min at 37°C, with or without pharmacologic inhibitors (apalrestat, PP2, N-acetyl-cysteine, pifithrin-μ). Platelets were then stimulated with normal glucose (NG, 5 mM) or HG (25 mM) for an additional 90 min. Functional assays were performed to evaluate SFN efficacy and investigate its underlying mechanisms.ResultsThe results demonstrated that SFN attenuated HG-induced platelet dysfunction by alleviating mitochondrial dysfunction (manifested as loss of mitochondrial membrane potential; p < 0.001), apoptosis (characterized by increased caspase-9/-3 activation and phosphatidylserine exposure; p < 0.01), and hyperreactivity (evidenced by enhanced aggregation and activation; p < 0.05). Mechanistically, SFN significantly suppressed HG-induced aldose reductase (AR) activity (p < 0.001). Pharmacological inhibition revealed that the beneficial effects of SFN on platelet function were mediated mechanistically through AR downregulation, which attenuated p53 phosphorylation via Src-dependent ROS generation.ConclusionThese findings suggest that by inhibiting the Src/ROS/p53 signaling pathway and mitigating AR-mediated platelet dysfunction, SFN may confer significant protection against atherothrombosis during hyperglycemia.